Case report: Optical genome mapping revealed double rearrangements in a male undergoing preimplantation genetic testing - Ren, Jun; Keqie, Yuezhi; Li, Yutong; Li, Lingping; Luo, Min; Gao, Meng; Peng, Cuiting; Chen, Han; Hu, Ting; Chen, Xinlian; Liu, Shanling (Frontiers in Genetics, 2023)
Chromosome rearrangement is one of the main causes of abortion. In individuals with double chromosomal rearrangements, the abortion rate and the risk of producing abnormal chromosomal embryos are increased. In our study, preimplantation genetic testing for structural rearrangement (PGT-SR) was performed for a couple because of recurrent abortion and the karyotype of the male was 45, XY der (14;15)(q10;q10). The PGT-SR result of the embryo in this in vitro fertilization(IVF) cycle showed microduplication and microdeletion at the terminals of chromosomes 3 and 11, respectively. Therefore, we speculated whether the couple might have a cryptic reciprocal translocation which was not detected by karyotyping. Then, optical genome mapping (OGM) was performed for this couple, and cryptic balanced chromosomal rearrangements were detected in the male. The OGM data were consistent with our hypothesis according to previous PGT results. Subsequently, this result was verified by fluorescence in situ hybridization (FISH) in metaphase. In conclusion, the male's karyotype was 45,XY,t(3;11)(q28;p15.4),der(14;15)(q10;q10). Compared with traditional karyotyping, chromosomal microarray, CNV-seq and FISH, OGM has significant advantages in detecting cryptic and balanced chromosomal rearrangements.